Badanie sprawozdań finansowych małych i średnich podmiotów gospodarczych - Kaczmarczyk, Angelika (Checking of Financial Reports in Small and Medium Entities, 2007)
According to the article 64 of Accounting Act the majority of small and medium entities is exempt from financial reports' examination by a chartered auditor. Therefore a question arises: Does the exemption from examination of financial reports decrease their credibility? Who, if not the chartered auditor, should be on guard of accounting books' reliability and reporting information s credibility of small and medium entities and credibility of security in economic turnover as well?
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1158, s. 222-228